Gastroenterite Aguda por Rotavírus em Portugal: Estudo Multicêntrico - Rodrigues, Fernanda (2015)
Introduction and aims: Considering the limited data on rotavirus (RV) disease in Portugal, this study aimed to estimate the proportion of RV acute gastroenteritis (AG) among Emergency Service (ES) visits in several centres in the country and characterise its clinical and molecular profile. Methods: Prospective, multicentre, observational study of children aged <5 years, with AG, attending ten paediatric ES, between October 2008 and September 2009. Demographic and clinical data were collected. RV positive samples were genotyped by PCR. Results: 1846 children were included, 58% male, mean age 19.3±14.4 months. Stools tested positive for RV in 28.3% (95% CI, 26.2-30.4%), with a higher prevalence in the winter and spring and in children aged 7 to 24 months. The most frequent genotypes were G4P[8] (46%) and G1P[8] (37%), with a geographical trend from north to south. Children with RVAG were more likely to have fever, vomiting, weight loss, dehydration and need for hospitalization (p<0,001 for all comparisons) and, therefore, more severe disease than RV negative cases. Conclusions: During the study period, RVAG in Portuguese children aged <5 years accounted for a great burden in the healthcare system, requiring care in the ES and hospitalisation. There were important differences in genotype prevalence among regions. In the era of RV vaccines, this knowledge is important for policy decisions concerning disease prevention and to monitor trends of RV molecular epidemiology.